O envolvimento da proteína cinase PAK1 na infecção pelo Orthopoxvirus vaccinia: implicações para a disseminação viral - Luciana Garcia Andrade (2012)
An efficient virus multiplication cycle results from a complex network of virus-host interactions culminating with a propitious intracellular environment for the generation and spread of virus progeny. Interfering with signaling pathways related to cytoskeleton dynamics is a common strategy employed by viruses to achieve this purpose. The Orthopoxvirus Vaccinia (VACV), the prototypic member of Poxviridae family, interacts in a complex way with both actin and microtubules cytoskeleton of their host cells during the whole replication cycle, and this manipulation is essential to assure the efficiency of viral entry, assembly, transport and dissemination. In the present study we investigated the possible involvement of serine/threonine kinase PAK1 (p21-activated kinase 1) upon VACV infection. To that end, mouse embryo fibroblasts (MEFs) derived from wild-type (WT) and PAK1-null (PAK1-/-) mice were infected with VACV at different times. We showed, through Western blotting assay and fluorescence microscopy, that PAK1 is not critically involved in the early steps of VACV cycle, and the need of PAK1 to VACV entry by macropinocytosis, previously described (Science, 320:531, 2008), does not affect the production of intracellular mature virus (IMVs). Although, we found that the absence of PAK1 led to a severe reduction in plaque phenotype and infections of MEFs PAK1-/- carried out at low-multiplicity were followed by a greatly reduced production (~90%) of both IMV and extracellular enveloped virus (EEV), indicating that virus spread was drastically impaired. Immunofluorescent staining of actin cytoskeleton and scanning electron microscopy showed a reduction in the number of VACV-induced actin tails in MEFs PAK1-/-, without alteration in the amount of cell-associated enveloped virus (CEVs). Furthermore, confocal microscopy of MEFs PAK1+/+ infected with VACV reveled a colocalization of P-PAK1 with actin tails tips as well as CEVs (B5R) particles. Indeed, these results show that PAK1 plays a role in actin-based motility of VACV, being an important cellular constituent to assure the efficiency of viral dissemination.